Obstacles to women’s adaptation and capacity- development in flood-affected areas of Bangladesh: a qualitative study - Nahar, Kamrun; Tajuddin, Nor Azlin; Sulaiman, Szariannie (Secholian Publication, 2024)
Women in Bangladesh are disproportionately affected by recurrent flooding events, which have a negative impact on them. Women are more susceptible and less adaptable than males in flood disasters due to socio-cultural barriers perpetuated by society. The objective of this research is to explore the challenges impede women’s ability to adapt and increase their capacity in flood-affected areas of Bangladesh. To accomplish this goal, a qualitative research approach was utilized, including Focus Group Discussions with six unique groups, and conducting In-depth interviews with a total of thirty participants. The research illustrates that women’s susceptibility issues are worsened by rural communities and flood disasters due to their lack of adaptability. This is mostly attributed to the patriarchal culture prevalent in rural Bangladesh, which poses challenges in acquiring the necessary knowledge, skills, resources, and capacity for adaption. Hence, this article argues in favour of the government’s unwavering commitment to effectively utilizing the complete potential of women to enhance their ability to adapt and integrate them into the broader fabric of society, thereby promoting positive societal progress by reducing their vulnerability.Adaptation Flood Capacity-building Bangladesh